Eating As Treatment (EAT) study protocol: a stepped-wedge, randomised controlled trial of a health behaviour change intervention provided by dietitians to improve nutrition in patients with head and neck cancer undergoing radiotherapy. Issue 7 (31st July 2015) - Britton, Ben; McCarter, Kristen; Baker, Amanda; Wolfenden, Luke; Wratten, Chris; Bauer, Judith; Beck, Alison; McElduff, Patrick; Halpin, Sean; Carter, Gregory
Abstract : Introduction: Maintaining adequate nutrition for Head and Neck Cancer (HNC) patients is challenging due to both the malignancy and the rigours of radiation treatment. As yet, health behaviour interventions designed to maintain or improve nutrition in patients with HNC have not been evaluated. The proposed trial builds on promising pilot data, and evaluates the effectiveness of a dietitian-delivered health behaviour intervention to reduce malnutrition in patients with HNC undergoing radiotherapy: Eating As Treatment (EAT). Methods and analysis: A stepped-wedge cluster randomised design will be used. All recruitment hospitals begin in the control condition providing treatment as usual. In a randomly generated order, oncology staff at each hospital will receive 2 days of training in EAT before switching to the intervention condition. Training will be supplemented by ongoing supervision, coaching and a 2-month booster training provided by the research team. EAT is based on established behaviour change counselling methods, including motivational interviewing, cognitive–behavioural therapy, and incorporates clinical practice change theory. It is designed to improve motivation to eat despite a range of barriers (pain, mucositis, nausea, reduced or no saliva, taste changes and appetite loss), and to provide patients with practical behaviour change strategies. EAT will be delivered by dietitians during their usual consultations. 400 patients with HNC (nasopharynx, hypopharynx, oropharynx, oral cavity or larynx), aged 18+, undergoing radiotherapy (>60 Gy) with curative intent, will be recruited from radiotherapy departments at 5 Australian sites. Assessments will be conducted at 4 time points (first and final week of radiotherapy, 4 and 12 weeks postradiotherapy). The primary outcome will be a nutritional status assessment. Ethics and dissemination: Ethics approval from all relevant bodies has been granted. Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: ACTRN12613000320752.